Potential use of the Maroua (Far North, Cameroon) river sand as construction materials and degreasing agent for earthenware ceramics - Mahamad Nafissatou; Bertin Pagna Kagonbé; Arnaud Ghislain Anombogo Mouthe; Bouba Nafissa; Viviane Djaoyang Bakaïné; Etienne Yanné; Likiby Boubakar; Armand Kagou Dongmo (Discover Applied Sciences)
Abstract There is an enhnaced accessibility of sand, which may be suitable for concrete and ceramic in different regions of Cameroon and the Far North in particular. Hence, this paper aims at assessing the properties of Maroua river sand and its prospects for use in building and probably in ceramic. Fieldwork and laboratory analyses have been performed to elicit their properties using standard methods of physical-textural analysis and X-ray fluorescence spectroscopy. Gradation parameters have been deduced mathematically. The results indicate that the grain size distribution varies slightly from one site to another. Organic matter content is relatively poor; it ranges from 0.26 to 0.67%. Sand equivalent (87.00–98.60) and fineness modulus (2.4–2.91) change to very clean and medium sand, respectively. The coefficient of uniformity and coefficient of curvature varies from 2.39 to 3.37 and 0.40 to 0.99, respectively, so it can be classified as a tightly-grained material. The most abundant oxides in the five samples are SiO2, Al2O3, and K2O, while Fe2O3, MgO, TiO2, and P2O5 are in small amounts except for CaO and Na2O which are present in high amounts in NS1, and NS2 samples. Globally, the studied sands have given satisfactory results, and they are suitable for use in concrete. Chemically, these sands can be used in the production of terracotta (pottery, bricks, tiles, and stoneware) as degreasers and fluxes, given the high percentage of K2O suitable for this group of ceramics.